Advancements in Antiviral Therapeutics: Strategies and Challenges in the Development of Drugs and Vaccines for Viral Diseases - Kaushiky Sharma (International Journal of Virus Studies, 2024)
Viral infections continue to pose a significant threat to global health, leading to high rates of illness, death, and economic burden. The constantly evolving nature of viruses, along with the rise of drug-resistant strains, underscores the need for continuous advancements in antiviral treatments. This review highlights the pivotal role of antiviral drugs and vaccines in mitigating the impact of viral infections, showcasing recent breakthroughs and exploring emerging technologies. Key advancements include the development of direct-acting antivirals (DAAs) targeting critical viral pathways, innovations in nanoparticle-based drug delivery systems, and transformative vaccine technologies like mRNA and vector-based platforms. Despite these strides, challenges such as drug resistance, accessibility disparities, vaccine hesitancy, and equitable distribution hinder optimal outcomes. Future directions in antiviral therapeutics emphasize the integration of artificial intelligence and bioinformatics for drug discovery, the promise of personalized therapies, and the potential of pan-viral therapeutics targeting broad-spectrum viral vulnerabilities. By addressing these challenges through interdisciplinary collaboration, the global community can achieve sustainable progress in combating viral diseases. This review aims to provide a comprehensive overview, inspiring continued innovation and strategic efforts in the field of antiviral therapeutics.
Keywords: Antiviral drugs; drug resistance; mRNA vaccines; pan-viral therapeutics; vaccine development